2008
DOI: 10.2310/6670.2008.00064
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Glomus Tumors: Comprehensive Review for Surgeons

Abstract: The diagnosis of a lower extremity glomus tumor (GT) is often delayed owing to the lack of awareness and low level of suspicion by the treating physician. GT is thought to arise from cutaneous arteriovenous connections, often involving the nail beds. The unusual location of the lower extremity often leads to missed or delayed diagnosis and management. Surgical excision of GT is often curative and provides significant symptomatic relief. There is a paucity of information in regard to GT in general, especially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Familial tumours are often inherited in an autosomal dominant manner. 6 Following a study of 32 cases, Carroll and Berman described a classical triad of symptoms that they felt were pathognomonic: 'spontaneous lancinating pain, extreme pain with the gentlest of touch, and intolerance to changes in temperature'. 4 Clinical tests such as the Love test (point tenderness) and Hildreth's sign (decreased pain on exsanguination of the limb and applying a tourniquet) have shown to be highly suggestive of glomus tumours, with Hildreth's sign having a sensitivity of 92%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Familial tumours are often inherited in an autosomal dominant manner. 6 Following a study of 32 cases, Carroll and Berman described a classical triad of symptoms that they felt were pathognomonic: 'spontaneous lancinating pain, extreme pain with the gentlest of touch, and intolerance to changes in temperature'. 4 Clinical tests such as the Love test (point tenderness) and Hildreth's sign (decreased pain on exsanguination of the limb and applying a tourniquet) have shown to be highly suggestive of glomus tumours, with Hildreth's sign having a sensitivity of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, all of the above tests may be negative, as demonstrated in a case report in 2005, in which the authors concluded that exploration of a painful finger should be considered if a glomus tumour is suspected even if the MRI findings are negative. 1,6,8 Surgical excision remains the standard treatment for glomus tumours, with clear margins indicating adequacy of treatment. However, if malignant features are suggested on histology, a wider excision is required as well as close follow-up review to assess for metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The benign perivascular neoplasm usually located in the distal limb, especially in the subungual (nail bed), as a localized blue-red nodules that are sensitive to cold and touch. Glomus tumor usually occurs in areas that are rich in glomus bodies such as digit or dermis in the palms, wrists, and forearms [ 7 , 9 , 10 ]. Thigh is not a specific location for glomus bodies, yet glomus tumor in thighs was reported and presented as bluish small nodule that are sensitive to touch and temperature changes [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate of subungual glomus tumor is 14%, due to the narrow and complicated surrounding structures which make it hard to differentiate the tumor from a normal tissue and excision in this area requires the surgeon to maintain the patient's nail matrix [ 12 , 16 ]. Glomus tumours in the thigh region rarely recurs since they are solitary and encapsulated, making them easily recognizable from the surrounding tissue [ 7 , 8 ]. In the six major published series, glomus tumor recurrence rates were ranging from 0% to 33.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation